A quasi-experimental study of lab rotation integrated with generative AI and peer code review model to enhance students’ critical thinking and academic resilience in introductory programming - Zheng, Weidong; Ratanaolarn, Thanin; Sriwisathiyakun, Kanyarat (My University, 2026)
Lab rotation provides a dynamic and interactive learning environment; generative artificial intelligence can help novices overcome learning challenges; and peer code review offers a collaborative learning environment. This study investigates how incorporating these designs into a new instructional model can enhance students’ critical thinking and academic resilience. A total of 83 first-year college students participated in the experiment, which lasted 6 weeks. The students were from two classes, majored in Educational Technology, and were enrolled in an introductory programming course titled ‘C Programming’. Class 1 was randomly selected as the control group and Class 2 as the experimental group. The experimental group and the control group were taught by the same teacher. The control group employed the traditional programming teaching method, whereas the experimental group utilized a new instructional model comprising four learning stations: instruction, lab, teacher-led, and review stations. All participants took a critical thinking test and an academic resilience questionnaire before and after the experiment. The results showed no significant difference in critical thinking and academic resilience between the pretest groups. In contrast, the post-test results showed that the experimental group’s critical thinking and academic resilience significantly outperformed those of the control group. The findings highlight the effectiveness of the instructional model on students’ critical thinking and academic resilience. This study is the first to integrate lab rotation, generative artificial intelligence, and peer code review into the design of a new instructional model for introductory programming and to demonstrate its effectiveness in enhancing students’ critical thinking and academic resilience. This study can serve as a reference for future studies.
Keywords: academic resilience; critical thinking; generative artificial intelligent; introductory programming; Lab rotation; peer code review